The Santa Fe Trail - Randolph, Ryan P. (New York : PowerKids Press, 2003)
Provides historical information about the founding of the Santa Fe Trail and about the lives and experiences of the people who used this route West.
Includes index.
6.5
3-6
Keywords: Santa Fe National Historic Trail -- History -- Juvenile literature; Frontier and pioneer life -- Santa Fe National Historic Trail -- Juvenile literature; Southwest, New -- Description and travel -- Juvenile literature; Santa Fe National Historic Trail; Frontier and pioneer life -- Southwest, New; Southwest, New -- History -- To 1848.; Santa Fe National Historic Trail; Frontier and pioneer life -- Southwestern States; Southwestern States -- History